Geração de lucro econômico e valor de mercado nas organizações não financeiras listadas na B3 - Oliveira, Daniela Batista de (2017)
From the advance of financial globalization and expansion of the stock market as a source of resources for economic development, competition in the capital search and maintenance has escalated, making the measurement of value creation for the shareholder an important process. Faced with uncertainties regarding the relationship between performance measurement mechanisms and company value, the study tried to highlight and analyze the relationship between both, working with the results of Brazilian organizations from 2010 to 2016. The problem that directed this research was: the generation of economic profit, as a measure of performance, is related with the market value of the organizations? The variables analyzed were: economic profit measured by operating profit and measured by net profit, market value, economic sector, size of Total Asset, life cycle and stock market liquidity. For the survey, 188 companies were selected in the period from 2010 to 2016. The statistical tests used were: Wilcoxon-Mann-Whitney mean difference test; the Kruskal-Wallis test with Bonferroni post-hoc; and regression analysis with panel data. In the first stage the results show that most of the companies presented economic losses, thus, there was no creation of value for the shareholder. The survey also reveals that there is statistical difference between the means of generating economic profit measured by the approach of operating profit and measured by net income. It is also observed that in 57% of the analyzed period, the economic sectors presented statistically equal means. Under the life cycle aspect, the results show that, in 71% of the analyzed period, the mean between the stages is statistically the same. Finally, the study found that in the model with the measurement of the operating profit, the variable economic profit was not statistically significant, indicating that it is not determinant for the companies' market value. Whereas, in the model with the measurement from the net profit, it was determined that the variable economic profit is statistically significant, which suggests that it is determinant for the market value of the companies. Thus, the main conclusions of the study are: (i) most Brazilian companies are not adding value; (ii) non-operating results contributed to leverage company results; (iii) the average economic result differs from the perspective of the economic sector and the life cycle of the companies; and (iv) the empirical evidence on the relationship between economic-financial performance measures based on value and the market value of organizations remain inconclusive, presenting conflicting results.